2020
DOI: 10.3389/fcell.2020.540726
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Composition and Activity Changes in Cultured Fibroblasts Derived From Mucopolysaccharidoses Patients and Their Modulation by Genistein

Abstract: In this study, we have asked whether proteasome composition and function are affected in cells derived from patients suffering from all types of mucopolysaccharidosis (MPS), an inherited metabolic disease caused by accumulation of undegraded glycosaminoglycans (GAGs). Moreover, we have tested if genistein, a small molecule proposed previously as a potential therapeutic agent in MPS, can modulate proteasomes, which might shed a new light on the molecular mechanisms of action of this isoflavone as a potential dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…Moreover, since some common patterns in gene expression ( Table 2 and Table 3 ) and organelles’ dysmorphology ( Figure 5 , Figure 6 , Figure 7 , Figure 8 and Figure 9 ) were observed, the detected changes should be considered reliable rather than random. In fact, reliability of studies based on the use of the same set of cell cultures has been indicated previously [ 8 , 9 , 10 , 11 , 19 ]. Another question can be asked whether fibroblasts are a good model, reflecting changes in MPS.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, since some common patterns in gene expression ( Table 2 and Table 3 ) and organelles’ dysmorphology ( Figure 5 , Figure 6 , Figure 7 , Figure 8 and Figure 9 ) were observed, the detected changes should be considered reliable rather than random. In fact, reliability of studies based on the use of the same set of cell cultures has been indicated previously [ 8 , 9 , 10 , 11 , 19 ]. Another question can be asked whether fibroblasts are a good model, reflecting changes in MPS.…”
Section: Discussionmentioning
confidence: 77%
“…However, documentation of anti-inflammatory activities of genistein is yet to be established. Additionally, due to the potential increase in residual activities of defective lysosomal enzymes that would otherwise be subjected to efficient ubiquitination and proteasomal degradation as misfolded proteins, the genistein-mediated reduction of proteasomal activities may have beneficial effects in mucopolysaccharidosis patients’ cells ( Pierzynowska et al, 2020 ). The most current findings from investigations on the use of genistein in various neurodegenerative disease models have described a focus on its autophagy-dependent activity ( Pierzynowska et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that the pathogenesis of LSDs is not limited to the primary cause—accumulation of the storage material. Such a hypothesis can be corroborated by recently published results demonstrating dysregulation of expression of hundreds of genes, coding for proteins involved in various cellular processes, in fibroblasts derived from patients suffering from mucopolysaccharidoses [ 51 , 106 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Ferroptosis Disorders As a Mechanism For Pathogenesis Of mentioning
confidence: 62%